Metal Dyshomeostasis and Their Pathological Role in Prion and Prion-Like Diseases: The Basis for a Nutritional Approach - Toni, Mattia; Massimino, Maria L.; De Mario, Agnese; Angiulli, Elisa; Spisni, Enzo (Frontiers in Neuroscience, 2017)
Metal ions are key elements in organisms’ life acting like cofactors of many enzymes but they can also be potentially dangerous for the cell participating in redox reactions that lead to the formation of reactive oxygen species (ROS). Any factor inducing or limiting a metal dyshomeostasis, ROS production and cell injury may contribute to the onset of neurodegenerative diseases or play a neuroprotective action. Transmissible spongiform encephalopathies (TSEs), also known as prion diseases, are a group of fatal neurodegenerative disorders affecting the central nervous system (CNS) of human and other mammalian species. The causative agent of TSEs is believed to be the scrapie prion protein PrPSc, the β sheet-rich pathogenic isoform produced by the conformational conversion of the α-helix-rich physiological isoform PrPC. The peculiarity of PrPSc is its ability to self-propagate in exponential fashion in cells and its tendency to precipitate in insoluble and protease-resistance amyloid aggregates leading to neuronal cell death. The expression “prion-like diseases” refers to a group of neurodegenerative diseases that share some neuropathological features with prion diseases such as the involvement of proteins (α-synuclein, amyloid β and tau) able to precipitate producing amyloid deposits following conformational change. High social impact diseases such as Alzheimer’s and Parkinson’s belong to prion-like diseases. Accumulating evidence suggests that exposure to environmental metals is a risk factor for the development of prion and prion-like diseases and that metal ions can directly bind to prion and prion-like proteins affecting the amount of amyloid aggregates. The diet, source of metal ions but also of natural antioxidant and chelating agents such as polyphenols, is an aspect to take into account in addressing the issue of neurodegeneration. Epidemiological data suggest that the Mediterranean diet, based on the abundant consumption of fresh vegetables and on low intake of meat, could play a preventive or delaying role in prion and prion-like neurodegenerative diseases. In this review, metal role in the onset of prion and prion-like diseases is dealt with from a nutritional, cellular and molecular point of view.